Association between maternal vitamin D deficiency and small for gestational age: evidence from a meta-analysis of prospective cohort studies. Issue 8 (27th August 2017) - Chen, Yao; Zhu, Beibei; Wu, Xiaoyan; Li, Si; Tao, Fangbiao
Abstract : Objective: To determine whether maternal vitamin D deficiency during pregnancy is associated with small for gestational age (SGA). Methods: A comprehensive literature search of PubMed, the Cochrane Library, Embase, and the Elsevier ScienceDirect library was conducted to identify relevant articles reporting prospective cohort studies in English, with the last report included published in February 2017. Pooled odds ratios (ORs) and corresponding 95% confidence intervals (CIs) were used to evaluate the correlation in a random effects model. Results: A total of 13 cohort studies were included in this meta-analysis with a sample of 28 285 individuals from seven countries. The pooled overall OR for babies born SGA was 1.588 ( 95% CI 1.138 to 2.216; p < 0.01) for women with vitamin D deficiency. The prevalence of vitamin D deficiency during pregnancy varied from 13.2% to 77.3%. Subgroup analyses identified no significant differences in the association between vitamin D deficiency and SGA based on study quality, gestational week during which blood sampling was performed, cut-off vitamin D levels, sample size, adjustment for critical confounders and method for measuring vitamin D. Conclusion: This meta-analysis suggests that vitamin D deficiency is associated with an increased risk of SGA.